Soil chemical quality in agricultural land uses in the semiarid of Bahia - Salviano, Alessandra Monteiro; Olszevski, Nelci; Arcoverde, Sálvio Napoleão Soares; de Melo, Stefeson Bezerra; Giongo, Vanderlise; Cunha, Tony Jarbas Ferreira; Pereira, Janielle Souza (Agrarian, 2018)
The aim of this work is to define indices of soil chemical quality in intense agricultural activity area surrounding Sobradinho Lake, State of Bahia, Brazil, by means of multivariate statistical techniques. Based on the factor scores, it was determined soil chemical quality index for depths of 0-0.10, 0.10-0.20 and 0.20-0.40 m, respectively, classifying soils as good, fair and poor, according to the performance of its attributes. Then realized the Discriminative Analysis in order to validate the results obtained and, knowing the chemical soil attributes that influence and are associated with soil quality in agriculture of the region. In this way, among the main results could be observed that the attributes exchangeable sodium percentage (ESP) and organic matter (OM) stood out as indicators of soil quality. The ESP was the more important attribute in discrimination models in the depths of 0.00-0.10 and 0.10-0.20 m and OM in the 0.20-0.40 m layer. These variables are the main responsible for discrimination and classification of soil groups. In general, the chemical quality of soils is not considered ideal mainly due to the low contents OM and the extremely sandy texture, denoting environmental fragility.